Effect of Tool Speed on Microstructure Evolution and Mechanical Properties of Friction Stir Welded Joints of Al-Mg-Si Alloy with High Cu Content - Wangzhen Li; Zhang Luo; Youping Sun; Xinyu Liu (Metals, 2024)
OM, SEM, EBSD, and other analytical techniques were utilized to investigate the effects of the rotating speed of a mixing head on the microstructures and mechanical properties of a joint. The results indicate that, compared with the base material, the grain size in the nugget zone is significantly refined. Furthermore, as the rotational speed of the mixing head increases, the grain size in the nugget zone increases noticeably, and the proportion of high-angle grain boundary length initially decreases and then increases. The texture types in different areas of the joint are markedly distinct: the base material primarily consists of recrystallization texture and rolling texture, while the core zone mainly comprises C-shear texture. Among the joints tested at various rotation speeds, the lowest hardness values are observed in the advancing side heat-affected zone, and the tensile properties of the joints are notably reduced due to the dissolution and coarsening of the second phase. The joint exhibits optimal performance at 1000 r/min, with a tensile strength and elongation of 196.3 MPa and 13.5%, respectively.